Observation on the efficacy of the combination of elevation and suspension techniques for boxcar acne scars - ZHUANG Yuchen; LIN Feiyan; YAN Tingting; SUN Dan; LIN Aiqing; HE Renliang; HUANG Lining; ZHU Dingheng (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To evaluate the clinical efficacy of elevation combined with suspension technique in the treatment of boxcar acne scars. [Methods] This split-face self-controlled study included 7 patients with boxcar acne scars who were treated at the Dermatology Hospital of Southern Medical University between January and May 2024. One side of patients′ face received only elevation treatment (the elevation group), while the other side received elevation surgery followed by suspension surgery (the combined group). The extent of improvement in scar was compared between the two groups one month after the treatment. [Results] At baseline, neither patient self-assessment scores of VAS nor physician assessment scores differed significantly between the two groups (VAS: 8.54±0.76 vs. 8.36±0.57, t=-0.52, P=0.614; physician assessment scores: 8.39±0.99 vs. 7.96±0.54, t=-1.00, P=0.336). One month after the treatment, more significant reductions in both patient self-assessment scores of VAS and physician assessment scores were observed in the group of combination therapy than in that of elevation alone (VAS: 6.21±1.01 vs. 3.40±0.69, t=5.97, P=0.001; physician assessment scores: 5.96±1.16 vs. 3.40±0.96, t=4.69, P=0.003). Moreover, both patient self-assessed efficacy and physician-evaluated efficacy were higher in the combination group than in the elevation group (both P<0.01). No significant adverse reactions were observed in either group. [Conclusion:] Although either combination of elevation and suspension methods or elevation alone is effective for boxcar acne scars, the former displays superior efficacy.